Crossed acoustic response combined with visual and somatosensory evoked responses in the diagnosis of multiple sclerosis. - Clifford-Jones, R E (1979)
The crossed acoustic response, (CAR), a recently introduced test of brainstem function, has been studied in 66 patients with multiple sclerosis and 53 control subjects, and compared with conventional visual and somatosensory evoked responses (VER, SER). A latency abnormality was found in the CAR in 73% of patients, in the VER in 63%, and in the SER in 37%. Abnormalities have been related to the presence or absence of clinically detectable signs. All three responses detected subclinical lesions by showing abnormality in a proportion of multiple sclerosis patients who had no corresponding abnormal clinical signs (CAR 69%, VER 42%, SER 29%). The best diagnostic combination of responses was VER and CAR. Ninety per cent of patients had at least one of these two responses abnormal.